Ma’na al-’Ilaj al-Nafsy wa Asalibuhu fi al-Turats al-Islamy - Muhammad Faqih Nidzom (Universitas Darussalam Gontor, 2019)
Soul therapy is one of the important issues in Islam. It has been greatly drawing the intention of majority Muslim scholars until now. By referring to their valuable works, this article tries to describe and analyze the concept of soul therapy in Islam. Ontologically, Muslim scholars believe that the soul, as one of the Almighty’s creations, should be always maintained, purified and heald when something goes wrong. Epistemologically, they explore the concepts and methods of this therapy from the singns given by the Qur’an and the explanation of the Prophetic traditions, which are all based on the Aqeeda Islamiyah, starting with the reconstruction of the concept and the worldview of oneself especially regarding the reality of himself. This brief study requires further research from the various brilliant works of the Muslim scholars as well as to elaborate comprehensively the concept of the soul and it’s therapy.